A pseudo-incremental rough set-based pseudo outer-product with ensemble learning (ieRSPOP++) fuzzy neural network - Iyer, Aparna. (2013)
Attribute and rule reduction through rough set theory in order to increase semantic interpretability is achieved in the rough set pseudo outer-product fuzzy neural network (RSPOP FNN); to improve the capability of RSPOP to function as an incremental system, an incremental ensemble RSPOP FNN is proposed. An incremental ensemble RSPOP FNN, named ieRSPOP, has been previously implemented; however ieRSPOP suffered from some problems: Hebbian Learning, multiple knowledge bases, storage of a huge chunk of data, and inflexible method to invoke rough set reduction.